Industry 4.0 and environmental accounting: a new revolution? - Roger Burritt; Katherine Christ (Asian Journal of Sustainability and Social Responsibility (AJSSR), 2016)
The paper seeks to examine how, through environmental accounting, the broader context of corporate sustainability could be incorporated into the developing vision for Industry 4.0, the fourth industrial revolution. An argument is developed that through engagement of the profession environmental accounting could be enhanced and could piggy-back at little extra cost on large actual and potential investments being made in Industry 4.0 infrastructure designed for digitisation of business. Industry 4.0 could be used successfully as a basis upon which to leverage both external environmental accounting and environmental management accounting. A new academic research program is suggested aimed at establishing how Industry 4.0 might facilitate more accurate, high quality, real time environmental management accounting and external environmental reporting in relevant sectors, company sizes, across different management roles and collaborative settings, as well as in supply and value chains. Ways are outlined in which accountants, professional associations and government can help capture the benefits of Industry 4.0 for environmental accounting. These include education and training opportunities and building on efficiency and lower cost notions which are a key part of Industry 4.0. This innovative paper provides first research into the potential of current and expected large investments throughout the world in Industry 4.0 to provide a foundation for improvements in corporate sustainability through greater take up of environmental accounting.
Keywords: 650; Industry 4.0; Environmental accounting; Environmental management accounting; External environmental reporting; Internet of Things; Internet of Services; Cyber-physical Systems; Transdisciplinarity